Effect of Heart Rate on the Outcome of Renal Denervation in Patients With Uncontrolled Hypertension - Böhm, Michael; Tsioufis, Konstantinos; Kandzari, David E.; Kario, Kazuomi; Weber, Michael A.; Schmieder, Roland; Townsend, Raymond R.; Kulenthiran, Saarraaken; Ukena, Christian; Pocock, Stuart; Ewen, Sebastian; Weil, Joachim; et al. (Journal of the American College of Cardiology, 2021)
Background: Sham-controlled trials demonstrated safety and efficacy of renal denervation (RDN) to lower blood pressure (BP). Association of baseline heart rate with BP reduction after RDN is incompletely understood. Objectives: The purpose of this analysis was to evaluate the impact of baseline heart rate on BP reduction without antihypertensive medications in the SPYRAL HTN-OFF MED (Global Clinical Study of Renal Denervation With the Symplicity Spyral Multi-electrode Renal Denervation System in Patients With Uncontrolled Hypertension in the Absence of Antihypertensive Medications) Pivotal trial. Methods: Patients removed from any antihypertensive medications were enrolled with office systolic blood pressure (SBP) ≥150 and <180 mm Hg and randomized 1:1 to RDN or sham control. Patients were separated according to baseline office heart rate <70 or ≥70 beats/min. BP changes from baseline to 3 months between treatment arms were adjusted for baseline SBP using analysis of covariance. Results: Scatter plots of 3-month changes in 24-hour and office SBP illustrate a wide range of changes in SBP for different baseline heart rates. Treatment difference at 3 months between RDN and sham control with baseline office heart rate ≥70 beats/min for 24-hour SBP was −6.2 mm Hg (95% CI: −9.0 to −3.5 mm Hg) (P < 0.001) and for baseline office heart rate <70 beats/min it was −0.1 mm Hg (−3.8 to 3.6 mm Hg) (P = 0.97) with an interaction P value of 0.008. Results were similar for changes in office, daytime, and nighttime SBP at 3 months, with a greater reduction in SBP with baseline office heart rate ≥70 beats/min. Conclusions: Reduction in mean office, 24-hour, daytime, and nighttime SBP for RDN at 3 months was greater with baseline office heart rate ≥70 than <70 beats/min, suggesting an association between baseline heart rate and BP reduction after RDN. (SPYRAL PIVOTAL—SPYRAL HTN-OFF MED Study; NCT02439749)
CRIS-Team Scopus Importer:2021-09-03
Keywords: blood pressure; heart rate; hypertension; renal denervation; sympathetic activation